Comprehensive Benefits Evaluation of Solar Water Heating System Application in Energy Efficiency Retrofit of Existing Residential Buildings in Cold Climate Zone. Issue 1 (January 2021) - Liu, Yiyang; Zhang, Meijie; Shen, Zebin
Abstract: The application of renewable energy in energy efficiency retrofit of existing residential buildings is very important for energy conservation and emission reduction. Promoting the application of solar water heating system is conducive to the construction of comprehensive technical system for energy efficiency retrofit of existing residential buildings. Based on the case study, this research uses the comprehensive benefits evaluation methods to evaluate solar water heating system application in energy efficiency retrofit of existing residential buildings in cold climate zone, and concludes that the payback period and internal rate of return are 13.5 years and 4.11% respectively. It is suggested that electricity should be chosen as the auxiliary energy of solar water heating system and the government should increase subsidies and develop incentive mechanisms to encourage the application of solar water heating system.